Effects of an Empowerment Program on the Knowledge, Empowerment Perception and First aid and Basic Screening of Disease Abilities Among Prison Health Voluntee - Inkaew, Thayuta; Rithpho, Pratuma; Buakhai, Pantipa (Journal of Public Health Nursing, 2019)
Prison health volunteers are important position to assist nurses in promoting public health in prisons. This one-group pretest posttest quasi - experimental design aimed to examine the effects of an empowerment program in first aid and basic screening of disease knowledge, empowerment perception, and their abilities. The 81 participants were recruited by purposive sampling. They were trained regarding to 25 hours divided 5 times of empowerment program including first aid and basic screening of disease. Data were collected at a Women Correctional Institution in Lower Northern part of Thailand and analyzed using The Friedman test and Wilcoxon Signed Ranks Test. The findings showed that prison health volunteers who received the empowerment program became more knowledgeable, empowered and able to provide first aid and basic screening of diseases in their role as health volunteers than before the empowerment program, and they remained knowledgeable and empowered when assessed again twelve weeks after receiving the program. This empowerment program is effective in promoting first aid and preliminary disease screening knowledge, empowerment perception, and abilities among prison health volunteers. Therefore, this program should be promoted to health volunteers in other prisons so that they will be able to deliver care to other inmates as expected by the prisons.